Philosophical horizons : metaphysical investigation in Chinese philosophy - Yang, Guorong, 1957- (Modern Chinese philosophy ;, 2019)
"Professor Yang Guorong is one of the foremost living philosophers in China, and is widely known for the development of his "concrete metaphysics." In Philosophical Horizons Yang offers penetrating discussions of some of the most important issues in modern philosophy--especially those topics related to comparative and Chinese philosophy. Drawing freely and adroitly on Confucian, Daoist, and Buddhist texts, while staging a dialogue with Western thinkers such as from Kant and Hegel to Marx, Heidegger, and Wittgenstein, Yang shows how contemporary Chinese philosophy has adopted, localized, and critically developed Western ideas alongside traditional Chinese concepts"--